2017
DOI: 10.1093/femsec/fix069
|View full text |Cite
|
Sign up to set email alerts
|

Greater diversity of soil fungal communities and distinguishable seasonal variation in temperate deciduous forests compared with subtropical evergreen forests of eastern China

Abstract: Whether and how seasonality of environmental variables impacts the spatial variability of soil fungal communities remain poorly understood. We assessed soil fungal diversity and community composition of five Chinese zonal forests along a latitudinal gradient spanning 23°N to 42°N in three seasons to address these questions. We found that soil fungal diversity increased linearly or parabolically with latitude. The seasonal variations in fungal diversity were more distinguishable in three temperate deciduous for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 55 publications
8
42
0
Order By: Relevance
“…Total and saprotrophic fungal community structures were more strongly related to soil factors in the desert. However, these fungal community structures were more strongly related to MAP in the grassland, which consistent with the findings of Shi et al (2014) and Timling et al (2014) . Although water availability has been considered as the key limited factor in dryland regions, we found MAP could only determine the fungal communities in the grassland.…”
Section: Discussionsupporting
confidence: 88%
“…Total and saprotrophic fungal community structures were more strongly related to soil factors in the desert. However, these fungal community structures were more strongly related to MAP in the grassland, which consistent with the findings of Shi et al (2014) and Timling et al (2014) . Although water availability has been considered as the key limited factor in dryland regions, we found MAP could only determine the fungal communities in the grassland.…”
Section: Discussionsupporting
confidence: 88%
“…Soil fungal community structure and their dominant phyla have differed in previous studies (He et al, ; Shi et al, ; Zhao et al, ). In our study, soil fungal taxonomic community structure differed between EBF and DBF, and the phylum Zygomycota was the most abundant in both DBF and EBF.…”
Section: Discussionmentioning
confidence: 87%
“…Chen et al () found that Zygomycota accounted for 45% of the phyla in primary stands of tropical rainforests. Some previous studies found that Ascomycota (Geml et al, ; He et al, ; Yang, Dou, Huang, & An, ) or Basidiomycota (Liu, Liu, Chen, Wang, & Zhang, ) were the dominant phyla in Andean Yungas forest, temperate deciduous forests and subtropical evergreen forests of eastern China, and Loess Plateau soil. Zygomycota are oligotrophic microbes (Zhao et al, ).…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, Tedersoo et al [22] found that Salicaceae plant phylogeny explained 75% of the variation in its EcM fungal richness. More studies demonstrated the strong influences of edaphic variables on fungal richness, such as pH [34,77], calcium [21], carbon [78], C/N ratio and phosphorus [38]. The effects of plant functional traits, such as the contents of rhizospheric exudates and litter chemistry [29,79], need to be addressed in future studies to be able to disentangle the plant-related effects.…”
Section: Effects Of Edaphic Variables and Plant Phylogeny On Fungal Rmentioning
confidence: 99%